Measurement of aerosol nanoparticles from a combustion particle generator by using three types of dilutors - Lee, Byung Uk; Bae, Gwi Nam (TURKISH NATL COMMITTEE AIR POLLUTION RES & CONTROL-TUNCAP, 2016)
Ultrafine aerosol nanoparticles created from combustion were measured by using three types of dilutors: a simple mixing dilutor, an ejector dilutor, and a rotational disk dilutor. The original particle size distribution from combustion was compared to the estimated distribution from these dilutors. The results showed that ultrafine aerosol nanoparticles maintained their particle size distribution, while particle concentrations decreased 10-20 fold in the dilution processes. Therefore, the dilutors not only diluted the aerosol nanoparticle concentration to the level of the measurement devices, but also helped estimate the shape of aerosol particle size distribution, particularly for ultrafine aerosol nanoparticles from combustion. Copyright (C) 2015 Turkish National Committee for Air Pollution Research and Control. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: ULTRAFINE PARTICLES; PARTICULATE-EMISSIONS; SIZE DISTRIBUTION; FINE